Armed Groups and the Environment in Cameroon: The Impact of Boko-Haram and Anglophone Secessionist on the Environment in Crisis Regions - Dinsi, Stanley Chung (European Journal of Applied Sciences, 2023)
Cameroon is blessed with a rich natural environment composed of the forest, rich and diversified biodiversity, soils rich in oil, gas and minerals, beautiful coasts and rivers. Since 2013, Cameroons’ environment has come under serious threats from the activities of Boko-Haram and Anglophone secessionist armed groups. This article assesses the impact of Boko-haram and the Anglophone secessionists on Cameroon’s environment including; the forest, animal and plant biodiversity, rivers, and the soil in crisis areas of the North, North West and South West regions respectively. But, how do non-state armed groups impact the environment and what are the perspectives for strengthening environmental protection? The study uses public policy and constructivism models to analyze legal and policy data on environmental protection and the environmental damages of Boko-Haram and Anglophone secessionists in the North, North West and South West regions of Cameroon respectively. Results of this study show that Bako-Haram and the Anglophone secessionist armed groups are a major cause of destruction of the forest and soil, water pollution and illegal exploitation of biodiversity in violation of international conventions and national conservation laws and policies. This study identifies concerted action of key stakeholders including; international organizations, the state of Cameroon, civil society actors and traditional authorities as a measure to orientate and strengthen environmental protection in Cameroon in crisis zones.